Beyond summerland [large type] - Lecoat, Jenny (Thorndike Press large print dynamic drama., 2024)
"The German occupation is over. The Channel Islands, the only occupied territory within the British Isles, are finally liberated. But now the local seek revenge on anyone suspected of collaborating with the enemy during the war. Nineteen-year-old Jean Parris is shocked to learn that Hazel, a teacher who lives above her dad's shop may be responsible for her father's wartime arrest. When Hazel learns of Jean's own secret, the women form an unexpected bond that sets them apart from the rest of Jean's family and the demands for retribution. But in the end, Jean's need to know the truth may consume everything she once believed about her home, her family, and herself"--